Empowerment of Shoes MSMEs Based on Technology and Financial Management - Albrian Fiky Prakoso; Djoko Suwito; Yunus (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
This Community Service activity aims to help UD.MM Collection in Sidoarjo who have problems with poor production management processes and financial management. This service method is in the form of providing shoe slip machines and financial management training through a simple cash book. The results obtained are UD. MM Collection can produce shoes faster because it already has a shoe slip machine with two slip sides, making it faster and more efficient. The results of the slip also have a smoother quality than the previous machine and save electricity. In addition, the machine is also equipped with a vacuum cleaner so that it is safer to use. The second result is UD. MM Collection can have neater financial records and know its financial position in terms of income, expenses, payables, and receivables.